The Effect of the Edu-Ecotourism Environment and Learning Motivation on Al-Qur’an Memorization Achievement in Al-Islah Islamic Boarding School - Abdul Azis; Mohamad Jaenudin; Amie Primarni (International Journal of Education, Information Technology, and Others, 2021)
This research was motivated by the low achievement of memorizing Al-Qur’an in educational institutions due to several factors, including; There is less interaction between teachers and students, there is no variation in forming a representative environment and students learning motivation is lacking in following the process of memorizing the Qur’an. This study aims to determine the extent of the influence of the Edu-Ecotourism Environment and Learning Motivation on Achievement of Memorizing the Qur’an in Al-Islah Islamic Boarding School. This research instrument uses a questionnaire and documentation. The research method used is descriptive quantitative method with multiple linear analysis, with a purposive sampling technique. Quantitative analysis includes validity and reliability tests, basic assumption tests, classical assumption tests, hypothesis testing using the f and t tests and the coefficient of determination (R2) analysis test. The result of the research is that the contribution of the Edu-Ecotourism Environment (X1) and Learning Motivation (X2) on Achievement of Memorizing the Qur’an (Y) is 82.4% and the remaining 17.6% is influenced by other variables not examined in this study. Ha is accepted, which means the Edu-Ecotourism Environment and Learning Motivation on Achievement of Memorizing the Qur’an in Al-Islah Islamic Boarding School